2014
DOI: 10.1213/ane.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

What Epidural Opioid Results in the Best Analgesia Outcomes and Fewest Side Effects After Surgery?

Abstract: Analgesic outcome, in terms of VAS pain score, was similar between the epidural opioids studied. These similarities in analgesia may reflect the common practices of concurrently using epidural local anesthetics with the opioids and titrating infusion rates according to a patient's pain status. With respect to side effects, the incidence of PONV and possibly pruritus was higher with morphine compared with fentanyl, despite there being similar total opioid consumption between those groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Meta-analyses have reported the benefits of using sufentanil, especially with respect to adverse effects. However, nausea, vomiting, and respiratory depression have also been reported as a result of overcompensation (Pöpping et al, 2012; Youssef et al, 2014). A multimodal analgesia that could enhance analgesia and reduce the requirement for opioids would be productive.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses have reported the benefits of using sufentanil, especially with respect to adverse effects. However, nausea, vomiting, and respiratory depression have also been reported as a result of overcompensation (Pöpping et al, 2012; Youssef et al, 2014). A multimodal analgesia that could enhance analgesia and reduce the requirement for opioids would be productive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite differences in pharmacokinetics and pharmacodynamics between opioids, 30 a recent meta-analysis by Youssef et al 31 demonstrated that the incidence of pruritus with neuraxial fentanyl is as high as that with neuraxial morphine. The incidence of pruritus in nonobstetric surgery patients after intrathecal morphine ranges from 15% to 70% 32-34 and after intrathecal fentanyl or sufentanil, from 53% to 79%.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in a concentration gradient in the cerebrospinal fluid with concurrent alterations in the rostral spread, resulting in increased systemic side effects if similar doses of morphine are used in a thoracic relative to lumbar epidural [43]. Late respiratory depression has been found to occur up to 24 h [44] [27] Sedation ++ [38,40], hypotension + [38] *: -= no reported neurotoxicity; + = at least some reported neurotoxicity or inconclusive data; ++ = multiple reports, neurotoxicity probable; +++ = multiple reports, almost certainly neurotoxic **: -= no reported side effects; + = mild effect; ++ = moderate effect; +++ = profound effect after an epidural dose. The incidence for delayed respiratory depression was found to be 0-2.8% [45], however a clear definition of respiratory depression is missing in the literature [45,46].…”
Section: Systemic Response and Respiratory Depressionhydrophilic Opioidsmentioning
confidence: 99%